Association of Contrast Enhancement After Reperfusion With Outcomes According to Blood Pressure Lowering in Patients With Acute Ischemic Stroke. (22nd November 2022) - Maïer, Benjamin; Brauner, Ran; Escalard, Simon; Gory, Benjamin; Lapergue, Bertrand; Sibon, Igor; Richard, Sebastien; Labreuche, Julien; Kyheng, Maeva; Desilles, Jean-Philippe; Blanc, Raphael; Piotin, Michel; et al.
Abstract : Background and Objectives: Observational studies described associations between higher systolic blood pressure (SBP) values and intracranial hemorrhages (ICHs) and worse outcomes after successful reperfusion by endovascular therapy (EVT). However, the BP-TARGET trial [BP-Target in Acute Ischemic Stroke to Reduce Hemorrhage after EVT] found that an intensive SBP target did not reduce ICH rates after successful EVT. The presence of contrast enhancement (CE) immediately after reperfusion is also associated with higher odds of ICH and worse outcomes. Our research question was to investigate the effect of 2 SBP strategies after reperfusion on ICH rates and functional outcomes according to the presence of CE in the BP-TARGET trial. We hypothesized that patients with CE could benefit from an intensive SBP control. Methods: We included BP-TARGET patients in whom a brain flat panel was performed immediately after reperfusion. We described CE as present or absent, ICH consisted of any radiographic ICH 24 hours after EVT, and unfavorable outcome consisted of a modified Rankin Scale score between 3 and 6 at 3 months. Results: Among the 324 patients randomized in BP-TARGET, 164 were included in this analysis, of whom 113 (68.9%) presented CE after reperfusion. The 24-hour mean SBP was significantly lower in the intensive SBP group compared with the standard group (129.7 vs 138.3 mm Hg, p < 0.001). Patients with CE and randomized in the intensive and standard SBP group had increased ICH rates: aOR = 11.26, 95% CI 4.59–27.63, and aOR = 4.08, 95% CI 1.75–9.50, respectively. However, the test of heterogeneity did not reach the significant level (aOR = 2.76, 95% CI 0.80 to 9.48, p = 0.11). Patients with CE and randomized in the intensive SBP group had also higher odds of unfavorable outcomes (aOR = 2.91, 95% CI 1.24–6.82), but this association was not significant in the standard SBP group (aOR = 1.89, 95% CI 0.85–4.23). No significant heterogeneity was found between the 2 groups (aOR, 1.54, 95% CI 0.48 to 4.97, p = 0.47). Discussion: Altogether, patients with CE and randomized in the intensive SBP group did not have lower rates of ICH or improved outcomes compared with the standard SBP group, as CE was associated with higher odds of ICH in both groups, without significant heterogeneity. Trial Registration Information: NCT03160677. Classification of Evidence: This study provides Class IV evidence that for adults with contrast-enhancing lesions after successful EVT of an AIS, intensive blood pressure management did not significantly increase the risk of ICH.